Design And Analysis Of Hexagonal Antenna For Uhf Rfid Reader - Nasrun Afiq, Adnan (2022)
The purpose of this paper is to present a design and analysis of hexagonal antenna for Ultra High Frequency (UHF) Radio Frequency Identification (RFID) Reader Application, to embrace the benefits offered by UHF RFID systems. In this design the FR-4 material is use to have medium, low cost and lightweight structure. The proposed antenna made up of hexagonal antenna patch and rectangular shape for the substrate. The antenna is meant to work on a frequency range of 919 MHz to 923 MHz, which is reserved for Malaysia's UHF RFID system. A voltage standing wave ratio (VSWR) of 1.14 and a gain of 5.87 at 921 MHz was obtained in CST microwave studio. The result of antenna parameter such as bandwidth, return loss and radiation pattern also discussed. Finally, this antenna will be tested with industrial UHF reader module and be able to read UHF tag data id manufactured by Avery Dennison that follow ISO 16000-C standards. All the parameter analysis was executed using CST Microwave Studio 2019 software.